Analisis Akurasi Model Tiga Dimensi Gedung Prof. H. Soedarto, SH. Menggunakan Teknologi Terrestrial Laser Scanner (TLS) Berbasis Metode Traverse - Yudo Prasetyo (TEKNIK, 2018)
The technology to record spatial building for conservation and spatial planning is growing rapidly. The urgency of the accuracy level in a measurement were set up higher than it used to. Three-dimensional object forming using Terrestrial Laser Scanner (TLS) equipment was one of the popular technologies among all. The TLS measurement method consists of 4 methods: Cloud to Cloud, Target to Target, Traverse, and hybrid method. This research aims to analyse the accuracy level of the Traverse method in measuring an 3D object for building documentation purposes using TLS. The accuracy level of Traverse method will be tested onto Building of Prof. Soedarto, S. H. There are two parameters used in validating the accuracy level of Traverse method: registration methods and visualization results of the three-dimensional model. The analysis result of point cloud data shows that TLS equipment applied with Traverse method is capable of producing 3D model of Building of Prof. H. Soedarto S. H. The obtained average validation value is 0.004 meters with the accuracy level of the RMSE model of ± 0.00611 meters